Swelling behavior and chemical stability of chitosan/nanocellulose biocomposites - Mohaiyiddin, Muhammad Safwan; Ong, Hui Lin; Othman, Muhammad Bisyrul Hafi; Julkapli, Nurhidayatullaili Muhd; Villagracia, Al Rey C.; Md. Akil, Hazizan (Wiley, 2018)
We investigated the chemical stability and swelling behaviour of synthesized biocomposites with varying concentrations of oil palm frond (OPF) nanocellulose and chitosan (Cs) for biomedical applications. Nanocellulose were extracted via acid hydrolysis method from OPFs and commercialized (COM) cellulose for comparative analysis. Condensation polymerization process was implemented to incorporate the nanocellulose and N, N’-Methylenebisacrylamide (MBA) crosslinker into the Cs. Flory-Huggin model was used to test their swelling behavior. Biocomposites in wet condition was observed through a variable pressure scanning electron microscopy (VP-SEM). Results showed that increasing the amount of nanocellulose on the biocomposites can reduce the swelling of the Cs, and it is significantly reduced (up to 420% at pH 4, up to 576% at pH 7, up to 305% at pH 10) with the use of OPF nanocellulose. Moreover, adding OPF nanocellulose to Cs has improved its stability in acidic medium, basic medium, aprotic solvent, polar solvent, non-polar solvent up to 90, 23, 23, 18, 22%, respectively. The swelling resistance and chemical stability of Cs biocomposites with OPF nanocellulose were better than using COM nanocellulose.